Perancangan Media Pembelajaran Informatika Menggunakan PowtoonDi MTsN 6 Agam - Salman Hamid Hamid (Jurnal Edik Informatika Penelitian Bidang Komputer Sains dan Pendidikan Informatika, 2023)
This research is motivated by the discovery of the problem that teachers have used learning media, namely Power Point. The use of Power Point is actually good but only focuses on writing so that the display becomes less attractive and students feel bored quickly. After conducting interviews with 5 students of MTsN 6 Agam, it can be concluded that the media used is less attractive so that students do not focus when participating in learning. They strongly agree that learning media is made more interesting so that students are more enthusiastic about participating in learning and do not feel bored.The type of research used is Research and Development (R&D). The research method used is the DDDE (Decide, Design, Develop, Evaluate) development model by Ivers & Barron (2002). The product tests carried out are validity tests, effectiveness tests and practicality tests. Based on the results of the research that the researchers did, the researchers succeeded in making informatics learning media using powtoon at MTsN 6 Agam. The results of the product test conducted by the researcher obtained a score of 0.88 in the valid category in the validity test by two computer experts and one linguist, and a very high score in the practicality test by three practitioners, obtaining a score of 0.93 in the high category and a score of 1 in the test. efficacy. A teacher and 30 students achieved a score of 0.86 in the high category.